2009
DOI: 10.1111/j.1526-4637.2009.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Pain Associated with Combat-Related Polytrauma

Abstract: Due to the high rates of blast injuries sustained during operations in Iraq and Afghanistan, the number of soldiers returning with massive and multiple wounds is unprecedented. While casualty survival rates have improved dramatically, the extent and impact of these wounds on soldiers' functioning pose unique challenges for their rehabilitation. Pain is highly prevalent in these individuals with polytrauma injuries and is a source of suffering, as well as an impediment to rehabilitation. However, there are a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 47 publications
1
53
0
1
Order By: Relevance
“…In another study of 50 OIF/OEF veterans treated at a Level 1 PRC, 80 percent incurred a combat-related TBI, 96 percent reported at least one pain problem, and 44 percent reported experiencing PTSD [5]. Clark and colleagues discussed the complex array of pain issues and the challenges related to the reliable assessment and care management of servicemembers being seen in the PRC [14]. Lew et al found that in a sample of the first 62 patients evaluated at a Level 2 PNS, 97 percent reported three or more PPCS (i.e., headache, dizziness, fatigue), 97 percent complained of chronic pain, and 71 percent met criteria for PTSD [4].…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 50 OIF/OEF veterans treated at a Level 1 PRC, 80 percent incurred a combat-related TBI, 96 percent reported at least one pain problem, and 44 percent reported experiencing PTSD [5]. Clark and colleagues discussed the complex array of pain issues and the challenges related to the reliable assessment and care management of servicemembers being seen in the PRC [14]. Lew et al found that in a sample of the first 62 patients evaluated at a Level 2 PNS, 97 percent reported three or more PPCS (i.e., headache, dizziness, fatigue), 97 percent complained of chronic pain, and 71 percent met criteria for PTSD [4].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate pain assessment is a necessary precursor to effective pain management. However, pain assessment can be challenging in polytrauma patients, especially in those with severe head injury, cognitive impairment, and multiple wounds (Clark, Scholten, Walker, & Gironda, 2009). The environment of the aircraft adds additional diffi culties to the assessment and documentation of pain.…”
Section: Innovations In Pain Managementmentioning
confidence: 99%
“…Nearly all tissues are of military interest, due to the diverse nature of injuries associated with war trauma (Figure 2). The increase in explosive attacks in current conflicts often results in massive wounds involving multiple organs [13], making all realms of tissue reconstitution a primary goal of military stem cell applications. To properly engineer complex tissues, stem cells will likely need to be augmented by biomaterials, which are not discussed in detail here (the authors recommend the following reviews: opinion on importance of synthetic biomaterials in tissue engineering [14]; current commercial biomaterials and future perspectives [15]; nerve guides [16]).…”
Section: Applications In Trauma and Regenerative Medicinementioning
confidence: 99%
“…Fracture stabilization, repair of vascular injury and tissue debridement often take precedence over nerve repair, and may lead to delays in addressing damaged nerves, further complicating peripheral nerve treatment [28]. In any type of nervous tissue injury, there is typically neuropathic pain, experienced as sharp, burning or stabbing sensations, which combined with limited motor recovery and subsequently limited functional recovery makes even partial restoration a clear goal [13]. …”
Section: Applications In Trauma and Regenerative Medicinementioning
confidence: 99%